Science Laboratory: A Student's Perception of Practicum Implementation at Junior High School - Rahmayumita, Restesa; Jannah, Miftahul; Novriandami, Aldila; Kusumasari, Anggi; Rahmad, M.; Linda, Roza (Asian Journal of Science Education, 2024)
The importance of practical implementation, especially in science subjects, is challenging for educators, students, and schools. Many findings are related to various obstacles and problems regarding implementing practicum in the laboratory, so the implementation is considered ineffective. This research aims to determine students' perceptions of implementing practicum in the science laboratory. This study used a survey method with a quantitative approach involving 96 respondents, consisting of 48 students in 8th grade at Junior High School 1 Kuantan Hilir and 48 students in 8th grade at Islamic Junior High School 1 Sentajo Raya. The instrument used was a questionnaire consisting of 26 statement items. The data collection technique was done by distributing questionnaires directly and then conducting descriptive analysis. The results of this study indicate that students' perceptions of the practical implementation in the science laboratory are in a good category (72.50%). In general, the practical implementation in the science laboratory for grade 8 students at Junior High School 1 Kuantan Hilir and Islamic Junior High School 1 Sentajo Raya has been carried out well. It can be concluded that students have a good perception of the implementation of practicum in the science laboratory.